The Effect of Concentration and Frequency of Neem Leaf Extract on Aphid Attacks on Chili Plants - Oktavianus Lumban Tobing; Yanyan Mulyaningsih; Amida Dwi Safitri (Indonesian Journal of Applied Research (IJAR), 2023)
Aphids that attack red pepper plants cause yield loss. Applying neem leaf extract in the form of concentration and frequency of yield losses can be avoided. Neem leaf extract contains secondary metabolite compounds that can function as vegetable insecticides to suppress the level of aphid attacks on chili plants. Saponins, meliantriol, and azadirachtin have been known as active ingredients that act as insecticides with different mechanisms of action against aphids, such as saponins as stomach poisons and contact poisons, meliantriol as a repellent (repellent/repellent), and azadirachtin as an inhibitor of ecdysone hormones (hormones that play a role in the process of metamorphosis or molting or exoskeleton of aphids). The study aimed to determine the effect of concentration and frequency of neem leaf extract on the incidence and severity of chili aphid attacks as well as plant development. The proposed solution to overcome aphid attacks is administering neem leaf extract to red chili plants. The method uses a randomized trial design of factorial groups with two factors. The first factor is the concentration of neem leaf extract which consists of four levels, namely: S0 = 0% (100 ml of water or without neem leaf extract), S1 = 10% (10 ml of neem leaf extract + 90 ml of water), S2 = 30% (30 ml of neem leaf extract + 70 ml of water), and S3 = 50% (50 ml of neem leaf extract + 50 ml of water). The second factor is the frequency of giving neem leaf extract, which consists of four levels: M1 = age 8 HSPT, M2 = age 16 HSPT, M3 = age 24 HSPT, and M4 = age 32 HSPT. The findings of this study are that the frequency of giving neem leaf extract three times showed a real effect on the severity of aphid attacks at the age of 44 days after transplanting, and giving a 10% extract had a real effect on height, leaf area, number of flowers, header dry bobobt, and dry weight of chili plant roots. The results of this study conclude that the administration of neem leaf extract can suppress the severity of the attack of red chili plant aphids.